Does Religious Involvement Mitigate the Effects of Major Discrimination on the Mental Health of African Americans? Findings from the Nashville Stress and Health Study - Ellison, Christopher G. (Religions, 2017)
Several decades of scholarly research have revealed the significant toll of discrimination experiences on the well-being of African Americans. Given these findings, investigators have become increasingly interested in uncovering any potential resources made available to African Americans for mitigating the psychosocial strains of discrimination. The current study contributes to this literature by testing whether various indicators of religious involvemente.g., church attendance, prayer, and religious social supportbuffer the noxious effects of major discrimination experiences on the mental health outcomes (i.e., depression and life satisfaction) of African Americans. We analyze data from the African American subsample (n = 627) of Vanderbilt University's Nashville Stress and Health Study, a cross-sectional probability sample of adults living in Davidson County, Tennessee between the years 2011 and 2014. Results from multivariate regression models indicated (1) experiences of major discrimination were positively associated with depression and negatively associated with life satisfaction, net of religious and sociodemographic controls; and (2) religious social support offset and buffered the adverse effects of major discrimination on both mental health outcomes, particularly for those respondents who reported seeking support the most often. We discuss the implications and limitations of our study, as well as avenues for future research.